Extraribosomal Functions of Cytosolic Ribosomal Proteins in Plants - Xiong, Wei; Lan, Ting; Mo, Beixin (Frontiers in Plant Science, 2021)
Ribosomes are basic translational machines in all living cells. The plant cytosolic ribosome is composed of four rRNAs and approximately 81 ribosomal proteins (RPs). In addition to the fundamental functions of RPs in the messenger RNA decoding process as well as in polypeptide synthesis and ribosome assembly, extraribosomal functions of RPs that occur in the absence of the ribosome have been proposed and studied with respect to RPs’ ability to interact with RNAs and nonribosomal proteins. In a few cases, extraribosomal functions of several RPs have been demonstrated with solid evidences in plants, including microRNA biogenesis, anti-virus defenses, and plant immunity, which have fascinated biologists. We believe that the widespread duplication RP genes in plants may increase the potential of extraribosomal functions of RPs and more extraribosomal functions of plant RPs will be discovered in the future. In this article we review the current knowledge concerning the extraribosomal functions of RPs in plants and described the prospects for future research in this fascinating area.